Membrane Localization of Human Equilibrative Nucleoside Transporter 1 in Tumor Cells May Predict Response to Adjuvant Gemcitabine in Resected Cholangiocarcinoma Patients. (31st March 2016) - Brandi, Giovanni; Deserti, Marzia; Vasuri, Francesco; Farioli, Andrea; Degiovanni, Alessio; Palloni, Andrea; Frega, Giorgio; Barbera, Maria A.; Lorenzo, Stefania; Garajova, Ingrid; Di Marco, Mariacristina; Pinna, Antonio D.; et al.
Abstract: Background: The use of gemcitabine as an adjuvant modality for cholangiocarcinoma (CC) is increasing, but limited data are available on predictive biomarkers of response. Human equilibrative nucleoside transporter 1 (hENT-1) is the major transporter involved in gemcitabine intracellular uptake. This study investigated the putative predictive role of hENT-1 localization in tumor cells of CC patients undergoing treatment with adjuvant gemcitabine. Methods: Seventy-one consecutive patients with resected CC receiving adjuvant gemcitabine at our center were retrospectively analyzed by immunohistochemistry for hENT-1 localization in tumor cells. The main outcome measure was disease-free survival (DFS). Hazard ratios (HRs) of relapse and associated 95% confidence intervals (CIs) were obtained from proportional hazards regression models stratified on quintiles of propensity score. Results: Twenty-three (32.4%) cases were negative for hENT-1, 22 (31.0%) were positive in the cytoplasm only, and 26 (36.6%) showed concomitant cytoplasm/membrane staining. Patients with membrane hENT-1 had a longer DFS (HR 0.49, 95% CI 0.24–0.99, p = .046) than those who were negative or positive only in the cytoplasm of tumor cells. Notably, the association between DFS and membrane hENT-1 was dependent on the number of gemcitabine cycles (one to two cycles: HR 0.96, 95% CI 0.34–2.68; three to four cycles: HR 0.99, 95% CI 0.34–2.90; five to six cycles: HR 0.27, 95% CI 0.10–0.77). Conclusion: hENT-1 localization on tumor cell membrane may predict response to adjuvant gemcitabine in CC patients receiving more than four cycles of chemotherapy. Further prospective randomized trials on larger populations are required to confirm these preliminary results, so that optimal gemcitabine-based chemotherapy may be tailored for CC patients in the adjuvant setting. Abstract : In patients with resected cholangiocarcinoma undergoing treatment with adjuvant gemcitabine, human equilibrative nucleoside transporter 1 (hENT-1) localization within tumor cells may be negative, positive in the cytoplasm only, or positive in both cytoplasm and membrane. Patients with hENT-1 in membrane had longer disease-free survival than the other groups, and the prediction was stronger with more cycles of gemcitabine.